World Investment Report 2007 - United Nations Conference on Trade; Development (United Nations, 2007)
The role of transnational corporations in extractive industries is attracting renewed attention, partly as a result of rising commodity prices and increased demand from emerging economies. This year, the World Investment Report examines TNC’s activities in extractive industries and their development implications. The Report explores policy options aimed at ensuring tangible and long-term gains for growth and development in developing countries. As usual, the first part of the Report reviews recent developments in global and regional FDI trends. Includes CD-ROM.